41st International Conference on Organizational Science Development: Society’s Challenges for Organizational Opportunities: Conference Proceedings (University of Maribor Press, 2022)
The four decades of the International Scientific Conference on the Development of Organizational Sciences are a period that brought together the academic and professional public, students, esteemed guests. The time and space are fundamental components of human life. The time of the epidemic introduces uncertainty among the people. That is why the individual of today together with the whole society, can set the building blocks for the social interweaving of society, as we are used to. We are an organization of people. Relationships between employees in organizations are the starting point for guidelines for the development of organizational sciences. This year’s conference is entitled “Values, Competencies and Changes in Organizations”. We’ll focus on the individual and the organization, which with common values co-create the integration and progress of the society. An individual who’ll cope with changes in the organizational view and the wider society with the proper competence frame. Precisely because of the many changes that have befallen us as a society, the international conference calls for the exchange of views, opinions and, above all, scientific views on the development of organizations in the future.